Language Kinship between Acehnese and Tamiang Malay Language - Cut Nuswatul Khaira; Tasnim Lubis (Tradition and Modernity of Humanity, 2024)
This study aimed to determine the percentage of kinship that exists between Acehnese and Tamiang Malay language and to find out the separation period of the two languages. This research was conducted using the quantitative method in which the data in this research is statistical. The techniques used in analyzing the data were lexicostatistical techniques. It was used to calculate the percentage of kinship between the two languages and also glotochronological techniques to calculate the separation time between Acehnese and Tamiang Malay language. The results of the study found that the percentage of kinship between Acehnese and Tamiang Malay is quite high, which is as much as 39%. From the results of calculations using glotochronology techniques that have been carried out, it is found that the separation period between Acehnese and Tamiang Malay language is as far as 1,616 years.